Design and Simulate Robotic Arm Structures from Dissimilar Materials Between T6061 Aluminum and Cast-Iron Alloy - Abd Razak , Muhammad Nor Aiman; Mohamed Salleh, Muhammad; Ghazali , Mohd Hafiz; Rohanai , Reyanhealme; Baharudin , Nurhayati (Research and Innovation in Technical and Vocational Education and Training, 2023)
Robotic arms have revolutionized numerous industries by providing efficient automation solutions for tasks that require high precision, dexterity, and reliability. This research paper delves into a comprehensive study centered around the design optimization of robotic arm structures, utilizing computer-aided design (CAD) software to seamlessly integrate dissimilar materials. The primary aim is to elevate performance levels by means of finite element analysis (FEA) simulations, which meticulously evaluate structural integrity, stress distribution, and deformation characteristics within the designed structures. By aligning these objectives, this research strives to unlock the full potential of robotic arm structures, revolutionizing their capabilities for superior industrial applications. The robotic arm design and simulation were conducted using SOLIDWORKS 2016, enabling a comprehensive evaluation of its structural integrity. Through an in-depth structural analysis, focusing on Von Mises stress and strain. This result highlights the critical role of material selection in reducing the weight of robotic arms. Despite the inherent strength advantages of cast iron alloys over aluminum alloys, an impressive 63% weight reduction was successfully achieved in the robotic arm. By employing static analysis with the finite element method (FEM), a detailed understanding of critical components within the robotic arm structures was obtained, leading to significant savings in terms of material resources, time, and costs.